PEMBERDAYAAN POTENSI WISATA PESISIR MELALUI PENYULUHAN BERBASIS MASYARAKAT DAN WORKSHOP PENATAAN WISATA DI KAMPUNG SKOW YAMBE, DISTRIK MUARA TAMI, KOTA JAYAPURA, PROVINSI PAPUA (PERBATASAN INDONESIA–PAPUA NUGINI): Empowering Coastal Tourism Potential through Community-Based Counseling and Tourism Arrangement Workshops in Skow Yambe Village, Muara Tami District, Jayapura City, Papua Province (Indonesia–Papua New Guinea Border) - Dani Arisandi DN; anita apriani; Muhtar Syam apriani; Ahmad Jafar apriani; Windy Jatmika apriani; Feane apriani; Wahyu kumala sari apriani (LPPM Universitas Muhammadiyah Papua, 2026)
Low community participation in tourism development remains a critical issue in many coastal and border areas, including Skow Yambe Village, Muara Tami District, Jayapura City, Papua Province. Despite its strategic location and rich coastal natural resources, the tourism potential of this village has not been optimally utilized to support local livelihoods. This Community Service Program (PKM) aimed to enhance community capacity and awareness in managing coastal tourism potential through counseling and tourism arrangement workshops. A participatory approach was employed, involving field exploration, observation, focus group discussions (FGDs), interactive lectures, group discussions, and question-and-answer sessions. The results indicate an increased level of community understanding regarding local tourism potential, the emergence of entrepreneurship intentions based on tourism activities, and a growing readiness of community members to actively participate in the development of a coastal tourism village. High levels of enthusiasm and positive responses from participants demonstrate the initial success of the program. This PKM activity provides a social and knowledge-based foundation for the sustainable development of Skow Yambe Village as a coastal tourism destination and contributes to improving community welfare in the Indonesia–Papua New Guinea border area.